Heavy metals and fertility - Gerhard, Ingrid; Monga, Bondo; Waldbrenner, Andreas; Runnebaum, Benno (Journal of toxicology and environmental health. Part A, 1998)
Heavy metals have been identified as factors affecting human fertility. This study was designed to investigate whether the urinary heavy metal excretion is associated with different factors of infertility. The urinary heavy metal excretion was determined in 501 infertile women after oral administration of the chelating agent 2,3-dimercaptopropane1-sulfonic acid (DMPS). Furthermore, the influence of trace element and vitamin administration on metal excretion was investigated. Significant correlations were found between different heavy metals and clinical parameters (age, body mass index, nationality) as well as gynecological conditions (uterine fibroids, miscarriages, hormonal disorders). Diagnosis and reduction of an increased heavy metal body load improved the spontaneous conception chances of infertile women. The DMPS test was a useful and complementary diagnostic method. Adequate treatment provides successful alternatives to conventional hormonal therapy.
Elektronische Reproduktion der Druck-Ausgabe 30. November 2010
Gesehen am 07.04.2025